2003
DOI: 10.1590/s0100-879x2003001100015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyproterone acetate on alpha1-adrenoceptor subtypes in rat vas deferens

Abstract: Gonadal hormones regulate the expression of α 1 -adrenoceptor subtypes in several tissues. The present study was carried out to determine whether or not cyproterone acetate, an anti-androgenic agent, regulates the α 1 -adrenoceptor subtypes that mediate contractions of the rat vas deferens in response to noradrenaline. The actions of subtype selective α 1 -antagonists were investigated in vas deferens from control and cyproterone acetate-treated rats (10 mg/day, sc, for 7 days). Prazosin (pA 2 ≈9.5), phentolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
(34 reference statements)
0
8
0
1
Order By: Relevance
“…α 1A ‐adrenoceptors are the main adrenoceptor subtype involved in the contractile responses to endogenous or exogenous agonists in the smooth muscle of the genitourinary system (Civantos Calzada and Aleixandre de Artinano, ) including the vas deferens (Campos et al, ), seminal vesicle (Silva et al, ), cauda epididymis (Queiroz et al, ) and prostate gland (Gray et al, ). This uroselectivity has driven the development of selective drugs for the treatment of benign prostatic hypertrophy (Ventura et al, ), and this receptor is also a target for male contraception (White et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…α 1A ‐adrenoceptors are the main adrenoceptor subtype involved in the contractile responses to endogenous or exogenous agonists in the smooth muscle of the genitourinary system (Civantos Calzada and Aleixandre de Artinano, ) including the vas deferens (Campos et al, ), seminal vesicle (Silva et al, ), cauda epididymis (Queiroz et al, ) and prostate gland (Gray et al, ). This uroselectivity has driven the development of selective drugs for the treatment of benign prostatic hypertrophy (Ventura et al, ), and this receptor is also a target for male contraception (White et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was observed that the remnant noradrenaline-induced contractions resistant to chloroethylclonidine treatment (40%) were readily blocked by an α 1A -antagonist 5-methyl-urapidil with high affinity (pA 2 of 8.8 to 8.9), in all conditions studied. It is well established that 5-methylurapidil interacts with higher affinity with α 1A -subtype (pA 2 of 9.0) than α 1B (pA 2 of 6.8) or α 1D (pA 2 of 7.3) subtypes (Ford et al 1997;Pupo et al 1997;Queiróz et al 2002;Campos et al 2003;Jurkiewicz et al 2006). Thus, these results indicate that noradrenaline-induced contractions of the testicular capsule are mediated by functional postsynaptic α 1A and α 1B -adrenoceptors, but pharmacological properties of these receptors were not influenced by sexual maturation or testosterone treatment.…”
mentioning
confidence: 99%
“…hormones are able to modulate the expression and/or function of α 1 -adrenoceptor subtypes in reproductive tissues (Queiroz et al 1999;Campos et al 2003). Campos et al (2003) showed that noradrenaline-induced contractions in the rat vas deferens are mediated by α 1 -adrenoceptor subtypes and this response is affected by in vivo treatment with cyproterone acetate, an anti-androgenic agent.…”
mentioning
confidence: 99%
See 2 more Smart Citations